Eating banitsa in London: Re-inventing Bulgarian foodways in the context of Inter-EU migration. (1st August 2019) - Ranta, Ronald; Nancheva, Nevena
Abstract: Based on interviews and surveys of Bulgarians living in the UK, the article explores the changing nature of Bulgarian foodways in the UK. Using banitsa, a 'traditional' Bulgarian breakfast dish, as the starting point for the research, the article examines the relationships Bulgarians in the UK have with their host and home communities as well as with their national identity and sense of belonging and the effect these have on their foodways and food consumption. The main claim the article makes is that the context of migration and of being a migrant engenders a deliberate attempt to foster and maintain an identity that is most often expressed in national terms, and most immediately performed in the everyday through food. Migrant belonging changes in such a way that the everyday becomes a means of identity construction and expression. Attitudes towards food - the making and serving of Bulgarian banitsa - illustrate this change.